601 The Effect of the COVID-19 Pandemic on Hip Fracture Mortality in The South West of England. (12th October 2021) - Spolton-Dean, C; Kent, B; Ball, T; Middleton, R; Marusza, C; Hinsley, H; King, A; Ayeko, S
Abstract: Aim: High perioperative mortality rates in surgical patients suffering concomitant COVID-19 infection have contributed to a fall in elective and urgent surgery. However, data and debate have centred around post hoc infected cases, without the context of the rest of the surgical cohort, and without comparable historical control groups. We aimed to address this by studying patients with a neck of femur fracture. This common condition has a stable incidence with good prospective data collected routinely for the National Hip Fracture Database (NHFD). Method: We analysed NHFD data for all hospitals within our region over a 3-month period, covering the height of the first outbreak and compared this with the same months in 2019. Results: The incidence of hip fracture was stable (463 in 2019, 448 in 2020). 30-day mortality was 6.26% in 2019 and 7.14% in 2020 (p = 0.595). In the second cohort, 14 patients tested positive for COVID-19 perioperatively. Of these, 3 died (21%) compared to 29 who tested negative (p < 0.001). Mean time to operation reduced by 1.90 hours, with a significant drop in patients waiting over 36 hours (190 to 85, p < 0.001). There were no significant differences between gender, ASA grade or pre-operative AMTS. Conclusions: We have confirmed high perioperative mortality for those with COVID-19 infection but have not shown a statistically significant difference in overall mortality from hip fracture during the initial phase of the pandemic. We argue from this data set that the hypothetical risk of surgery during this pandemic may have been overestimated.